2006
DOI: 10.3177/jnsv.52.473
|View full text |Cite
|
Sign up to set email alerts
|

Dose Dependent Elevation of Plasma Tocotrienol Levels and Its Effect on Arterial Compliance, Plasma Total Antioxidant Status, and Lipid Profile in Healthy Humans Supplemented with Tocotrienol Rich Vitamin E

Abstract: Summary Tocotrienols are a class of vitamin E reported to be potent antioxidants, besides having the ability to inhibit the HMG-CoA reductase enzyme. This study assessed the effects of 3 doses of tocotrienol-rich vitamin E (TRE) on plasma tocotrienol isomer concentration, arterial compliance, plasma total antioxidant status (TAS), aortic systolic blood pressure (ASBP), serum total cholesterol (TC) and low density lipoprotein cholesterol (LDL-C) in healthy males. Methodology: This randomised, blinded end-point,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 28 publications
1
50
1
Order By: Relevance
“…Purified TTs and ␣-TOC concentrations are reported in Table 1. Concentrations of TTs used in the experiements were in the micromolar order, which is a concentration that can be achieved in the human serum, as reported previously (36,53,76). Control cells were treated with the same volumes of DMSO and/or ethanol vehicle alone.…”
Section: Methodsmentioning
confidence: 99%
“…Purified TTs and ␣-TOC concentrations are reported in Table 1. Concentrations of TTs used in the experiements were in the micromolar order, which is a concentration that can be achieved in the human serum, as reported previously (36,53,76). Control cells were treated with the same volumes of DMSO and/or ethanol vehicle alone.…”
Section: Methodsmentioning
confidence: 99%
“…Concentrations reported for TTs and a-TOCO are related to the percentage present in the PTRF mixture. Concentrations of TTs used in the experiments were in the micromolar order, which is a concentration that can be achieved in the human serum, as described previously [16]. Control cells were treated with the same volumes of DMSO and/or ethanol vehicle alone.…”
Section: Cells Lines and Treatmentsmentioning
confidence: 99%
“…Rasool et al (2006) employed similar TTMF products at dosages 80, 160 and 320 mg daily for two months in healthy males and found that TTMF had neutral effects on arterial compliance, total antioxidant status and lipids [29]. The neutral effects of these combined supplementations on lipids and inflammation is further supported by another Chinese group.…”
Section: Discussionmentioning
confidence: 95%